Comparing Different CFD Methods Accuracy in Computing Local Boundary Layer Properties - Pettersson, Karl; Rizzi, Arthur (Engineering Applications of Computational Fluid Mechanics, 2009)
In aeronautical applications wind tunnels are often not capable of producing high Reynolds numbers which are achieved at free flight conditions. Today CFD methods are often used as a tool to estimate scale effects. CFD methods are commonly used to predict flow features at Reynolds numbers higher than what the aircraft model is subject to in the wind tunnel, and at higher Reynolds number than the turbulence model has been calibrated to. The investigation of local boundary layer properties could give useful information when the wind tunnel data is scaled to free flight conditions-the question is whether the CFD methods compute these in a consistent manner when there is a large spread in Reynolds number. This work compares two different CFD solvers and two different turbulence models' accuracy in computing local boundary layer properties compared to wind tunnel measurements.